PERAN KANTOR URUSAN AGAMA (KUA) DAN TOKOH MASYARAKAT DALAM MENCEGAH PERNIKAHAN DINI DI KECAMATAN LIBURENG KABUPATEN BONE TAHUN 2020-2021: Bahasa Indonesia - Fajar Nessa; Asni; Zulhasari Mustafa (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
Abstract In writing this thesis, the research was conducted with the aim of knowing 1. The role of the Office of Religius Affairs in Preventing Early Marriage in Libureng District, Bone Regency. 2. The Role of Community Leaders in Preventing Erly Marriage.This Research is Classified as field research or field research with the research approach used is the syar’i and empirical approach. The data sources of this research are primary data sources and secondary data by conducting interviews with several communities in Libureng sub-district, especially in Ponre-Ponre Village. The data analysist technique used is qualitative analysist, namely analyzing data by describing in detail the reality or reality of an object in the from of sentences. The result showed that (1) Efforts made by the Office of Religious Affairs Libureng District, Bone Regency in Preventing Early Marriage, namely Socialization with the Community that Underage marriage is not allowed and Conducting a Guidance Program for Community Leaders in order to minimize the very high rate of early marriage. Concerning (2) the role of community leaders in preventing early marriage, namely, getting involved in socialization about early marriage, in collaboration with the health sector, forming Youth Family Development, in collaboration with religious leaders and every villager is required to come to the village hall to take care of the administration marriage license.The cause of early marriage is due to the disharmony of a family member relationship, and the exsistence of economic factors, eeducation, customs, namely by getting their children married even though they are still underage.The implication of this research is that it is necessary to conduct socialization related to the marriage law and convey the negative impacts of early marriage and institutions should be selective because many people still do not know that underage marriage is not allowed. Keywords: Religious Affairs Office, Prevention, Early Mariage